2007
DOI: 10.1016/j.jml.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

On the give and take between event apprehension and utterance formulation

Abstract: Two experiments are reported which examine how manipulations of visual attention affect speakers' linguistic choices regarding word order, verb use and syntactic structure when describing simple pictured scenes. Experiment 1 presented participants with scenes designed to elicit the use of a perspective predicate (The man chases the dog/The dog flees from the man) or a conjoined noun phrase sentential Subject (A cat and a dog/A dog and a cat). Gaze was directed to a particular scene character by way of an atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
407
6
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(457 citation statements)
references
References 50 publications
41
407
6
3
Order By: Relevance
“…This definition of perceptual guidance is compatible with that of visual saliency (Itti & Koch, 2000;Parkhursta, Lawb, & Niebur, 2002). Saliency, as a composite measure of low-level visual information, is positively correlated with the presence of objects (Elazary & Itti, 2008), and found to guide attention in tasks where targets are underspecified (e.g., memorization, Underwood & Foulsham, 2006), and also utilized during situated language production (Gleitman et al, 2007). In our view, the most appropriate way to define visual saliency is in terms of visual clutter, calculated by integrating low-level visual information, e.g., color, with edge information (Rosenholtz, Mansfield, & Jin, 2005).…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…This definition of perceptual guidance is compatible with that of visual saliency (Itti & Koch, 2000;Parkhursta, Lawb, & Niebur, 2002). Saliency, as a composite measure of low-level visual information, is positively correlated with the presence of objects (Elazary & Itti, 2008), and found to guide attention in tasks where targets are underspecified (e.g., memorization, Underwood & Foulsham, 2006), and also utilized during situated language production (Gleitman et al, 2007). In our view, the most appropriate way to define visual saliency is in terms of visual clutter, calculated by integrating low-level visual information, e.g., color, with edge information (Rosenholtz, Mansfield, & Jin, 2005).…”
Section: Introductionsupporting
confidence: 63%
“…The interaction between visual attention and sentence processing could potentially take place in a number of ways, and a wide variety of factors have been identified, both linguistic (e.g., Meyer et al, 1998;Griffin & Bock, 2000;Bock et al, 2003;Kuchinksy et al, 2011) and perceptual (e.g., Gleitman et al, 2007;Papafragou et al, 2008;Myachykov et al, 2011). Language production is sensitive to simple perceptual events (e.g., a light flash at the target location, Gleitman et al, 2007), but also interacts with complex perceptual information, such as the type of motion depicted (influencing whether manner or path verbs are produced (Papafragou et al, 2008), or the complexity of the depicted event (influencing grammatical role assignment and linear position, Myachykov et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If these roles are not assigned, then a locative structure is inappropriate. Furthermore, it is thought that the relative salience of arguments can determine structural choices independently of the verb (Bock 1982;Gleitman, January, Nappa & Trueswell, 2007;Goldberg, 1995). Indeed, Gropen et al (1991a) demonstrated that changes in the salience of LOCATION and THEME at test did change Figure 1.…”
Section: )mentioning
confidence: 99%